Kemampuan Komunikasi Matematis ditinjau dari Self-Esteem Siswa SMP pada Materi SPLDV - Ramadhani, Safitri; Oktaviana, Dwi; Prihatin, Iwit (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to assess the mathematical communication abilities of junior high school students regarding self-esteem with the topic of two-variable linear equation systems. The research method used is descriptive qualitative research. The participants in this study are ninth-grade students at SMP Yakhalusti in Pontianak. This study uses measurement techniques, direct communication strategies, and indirect communication techniques for data collection. The subjects in this study are class IX A students of SMP Yakhalusti Pontianak, totaling 28 students selected using purposive sampling. Meanwhile, for data analysis subjects, 6 students were chosen based on criteria of high, medium, and low self-esteem. The research findings show that students with high self-esteem fulfill three indicators of mathematical communication skills: the capacity to translate mathematical concepts into real objects and images (drawing), the ability to articulate situations as mathematical expressions, and the proficiency to explain and convey mathematical ideas in written form using their own language. Students with moderate self-esteem met two indicators: the ability to reflect mathematical ideas into tangible objects and images (drawing) and the capacity to explain and express mathematical ideas in writing in their own language. In contrast, students with low self-esteem did not meet any of the three indicators of mathematical communication ability: drawing, mathematical expression, and written text.